Development and Innovation of Multimedia Courseware for Teaching and Learning of KAFA Subjects - Wan Malini, Wan Isa (2010)
Nowadays, the development of technology is affecting the educational sector. Courseware is one of the approaches that can be used in teaching and learning process so that it becomes more effective and interesting. This paper demonstrates the process of development of multimedia courseware that can be used for teaching and learning of KAFA subjects. Development of the courseware is to deal with some issues that arise in teaching and learning of KAFA subjects. The courseware is developed based on selected methodology to ensure that it fulfills the teaching and learning objectives. It is integrated with multimedia elements such as graphics, audio and video to make it more attractive to be used by students in their learning process